Modulating chitosan-PLGA nanoparticle properties to design a co-delivery platform for glioblastoma therapy intended for nose-to-brain route - Ferreira, Natália N. [UNESP]; Granja, Sara; Boni, Fernanda I. [UNESP]; Prezotti, Fabíola G. [UNESP]; Ferreira, Leonardo M. B. [UNESP]; Cury, Beatriz S. F. [UNESP]; Reis, Rui M.; Baltazar, Fátima; Gremião, Maria Palmira D. [UNESP] (Springer Nature, 2020)
Nose-to-brain delivery is a promising approach to target drugs into the brain, avoiding the blood-brain barrier and other drawbacks related to systemic absorption, and enabling an effective and safer treatment of diseases such as glioblastoma (GBM). Innovative materials and technologies that improve residence time in the nasal cavity and modulate biological interactions represent a great advance in this field. Mucoadhesive nanoparticles (NPs) based on poly(lactic-co-glycolic acid) (PLGA) and oligomeric chitosan (OCS) were designed as a rational strategy and potential platform to co-deliver alpha-cyano-4-hydroxycinnamic acid (CHC) and the monoclonal antibody cetuximab (CTX) into the brain, by nasal administration. The influence of formulation and process variables (O/Aq volume ratio, Pluronic concentration, PLGA concentration, and sonication time) on the properties of CHC-loaded NPs (size, zeta potential, PDI and entrapment efficiency) was investigated by a two-level full factorial design (24). Round, stable nano-sized particles (213–875 nm) with high positive surface charge (+ 33.2 to + 58.9 mV) and entrapment efficiency (75.69 to 93.23%) were produced by the emulsification/evaporation technique. Optimal process conditions were rationally selected based on a set of critical NP attributes (258 nm, + 37 mV, and 88% EE) for further conjugation with CTX. The high cytotoxicity of CHC-loaded NPs and conjugated NPs was evidenced for different glioma cell lines (U251 and SW1088). A chicken chorioallantoic membrane assay highlighted the expressive antiangiogenic activity of CHC-loaded NPs, which was enhanced for conjugated NPs. The findings of this work demonstrated the potential of this nanostructured polymeric platform to become a novel therapeutic alternative for GBM treatment. [Figure not available: see fulltext.].
Keywords: Cetuximab; Chicken chorioallantoic membrane assay; Glioblastoma; Nanotechnology; SW1088 glioma cell line; U251 glioma cell line; α-Cyano-4-hydroxycinnamic acid